Pengaruh Pemungutan Pajak atas Transaksi Cryptocurrency dan Literasi Keuangan terhadap Niat Berinvestasi pada Cryptocurrency - Dewi Kusuma Wardani; Erika Violenta Pesirahu (SAFE-Network, 2023)
The transformation of information technology gave birth to the latest innovations, one example of which is public access to the financial transaction sector. The purpose of this study is to determine the effect of tax collection on cryptocurrency transactions and financial literacy on the intention to invest in cryptocurrency. This research uses a type of research using quantitative methods whose data uses statistical analysis and uses numbering. The population used in this study is all millennial generation in the istmewa area of Yogyakarta. The sample used for this study was a millennial generation with an age range of 18-50 years totaling 114 people. Sample collection technique with snowball sampling model where the distribution of questionnaires to resonence is carried out online, how to distribute questionnaires using social media (WhatsApp, Twitter, and Instagram). The study used multiple linear regression analysis. In the research that has been done, it can be concluded that tax collection on cryptocurrency transactions does not have an influence on investment intentions. Financial literacy has a positive influence on the intention to invest in cryptocurrencies. The results of research and discussion of each variable illustrate that financial literacy has an influence on the intention to invest in cryptocurrency for respondents, most of whom are students. This proves that financial literacy such as understanding and skills in managing finances have been applied well by students when deciding to invest.